Фрагмент национальной языковой картины мира в повести Николая Гоголя Шинель - Соболева, Галина (Acta Polono-Ruthenica, 2021)
This article discusses the peculiarities of the linguistic representation of the 19th century St. Petersburg as understood by the individual author. Through the analysis and description of the lexical units of the novel against a wide historical background, it is possible to reconstruct the details of the life of the city. Facts of a social, domestic, and cultural nature are revealed through a close examination of the writer’s idiosyncratic language, including fixed collocations, jargon words and names created by Gogol himself. The lexeme “shinel” and its various descriptions in accordance with civilian ranks, as well as other names contextually related to this uniform, are also examined.